The most complete political machine ever known the North's Union Leagues in the American Civil War - Taylor, Paul 1959- (Kent State University Press, 2018)
"This book in the Civil War in the North series examines the Union League movement and its influence on the Northern home front in the Civil War."...Provided by publisher
Includes bibliographical references and index
Keywords: Union League of America; Patriotic societies -- United States; Political culture -- Northeastern States -- History -- 19th century; Nationalism -- United States -- History -- 19th century; Patriotism -- United States -- History -- 19th century; Sezessionskrieg -- 1861-1865; United States -- History -- Civil War, 1861-1865 -- Political aspects; United States -- History -- Civil War, 1861-1865 -- Social aspects; Northeastern States -- Politics and government -- 19th century; Northeastern States -- Social conditions -- 19th century